REINTERPRETATION OF POLYGAMY VERSES IN HERMENEUTIC PERSPECTIVE OF HANS GEORGE GADAMER - Masruchin, Masruchin; Abdul Malik Ghozali; Rani Larasati (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
Polygamy is an issue discussed and constantly studied, especially by understanding the Surah An-Nisa verse 3, where the textual meaning of polygamy opens up a wide opportunity for acts of violence to be experienced by wives, both psychologically and non-psychological. Therefore, this study aimed to examine the contextual meaning of polygamy by using Hans George Gadamer's hermeneutical approach, which is rich in contextual studies. The author employed a library research method with descriptions and interpretations to produce a consistent and comprehensive understanding. Through Gadamer's hermeneutical approach, the authors found that women in polygamous marriages do not mean that they are weak and deserve harsh treatment. Instead, they need to be protected and raised their dignity so that polygamy only applies to widows and orphans who cannot afford it.